Dimensions necessitated for total service operations management (TSOM) / Ardiana Mazwa Raudah Amir Abdullah … [et.al.] - Amir Abdullah, Ardiana Mazwa Raudah; Abdullah, Firdaus; Voon, Boo Ho; Matthew, Vloreen Nity; Abg Mohar, Abg Hamizam (2014)
The service industry has played an increasingly significant role in many economies and is no different to the Malaysian economy, contributing positively to the Gross Domestic Product (GDP), with a steady and consistence annual increase compared to the manufacturing sector. The growth of the Malaysian economy has also witness an increasingly aggressive competition among service providers in all different segments to survive and achieve competitive advantage. The increasing market dynamism has forced service providers to adapt to ensure survival. Failure to adapt will led to inability to sustain competitions and may affect survival. Vast studies in manufacturing areas have empirically indicated operational practices deployed have resulted in superior operational performances. As such operational practices has been commonly seen by service providers as a tools to achieve competitive advantage.